Expression of a gene encoding a 16.9-kDa heat-shock protein, Oshsp16.9, in Escherichia coli enhances thermotolerance - Yeh, Ching-Hui (The National Academy of Sciences of the USA, 1997)
A gene encoding the rice 16.9-kDa class I low-molecular-mass (LMM) heat-shock protein (HSP), Oshsp16.9, was introduced into Escherichia coli using the pGEX-2T expression vector to analyze the possible function of this LMM HSP under heat stress. It is known that E. coli does not normally produce class I LMM HSPs. We compared the survivability of E. coli XL1-Blue cells transformed with a recombinant plasmid containing a glutathione S-transferase (GST)–Oshsp16.9 fusion protein (pGST-FL cells) with the control E. coli cells transformed with the pGEX-2T vector (pGST cells) under heat-shock (HS) after isopropyl β-d-thiogalactopyranoside induction. The pGST-FL cells demonstrated thermotolerance at 47.5°C, a treatment that was lethal to the pGST cells. When the cell lysates from these two E. coli transformants were heated at 55°C, the amount of protein denatured in the pGST-FL cells was 50% less than that of the pGST cells. Similar results as pGST-FL cells were obtained in pGST-N78 cells (cells produced a fusion protein with only the N-terminal 78 aa in the Oshsp16.9 portion) but not in pGST-C108 cells (cells produced a fusion protein with C-terminal 108 aa in the Oshsp16.9 portion). The acquired thermotolerant pGST-FL cells synthesized three types of HSPs, including the 76-, 73-, and 64-kDa proteins according to their abundance at a lethal temperature of 47.5°C. This finding indicates that a plant class I LMM HSP, when effectively expressed in transformed prokaryotic cells that do not normally synthesize this class of LMM HSPs, may directly or indirectly increase thermotolerance.